"He looks gorgeous" – iuMR images and the transforming of foetal and parental identities. Issue 2 (18th November 2018) - Lie, Mabel; Graham, Ruth; Robson, Stephen C; Griffiths, Paul D
Abstract: The MERIDIAN study examined whether in‐utero MRI (iuMRI) improves the accuracy of diagnosis of foetal brain abnormalities, when used as an adjunct to ultrasound anomaly scanning. A diagnostic iuMRI differs from routine ultrasound screening because of its infrequent use and scanning procedure. Nested within this trial, this sociological study explored the acceptability of iuMRI as a technology and its contribution to parental decision‐making. Our sociological interpretation of the role of iuMR images in prenatal diagnosis draws on narrative interviews with women (and some partners) who underwent MRI imaging at three different centres. Overall, participants found iuMRI helpful in decision‐making because it either confirmed or disconfirmed previous results, or provided additional information. Expectant couples experienced the iuMR imaging process as informative, but also as having emotive and practical value. Our paper extends the existing sociological literature on antenatal testing and visualising the foetus, by using iuMR diagnostic imaging to further explore the concept of the unborn entity. Our data suggest that alongside the iuMR images, the 'parental gaze' and accompanying commentary are used by parents to construct and transform foetal and parental identities despite ongoing uncertainties about, and shifting social contexts to their pregnancy.